Fields of synergy - theory and practice of cooperation between social enterprises and business - Pachura, Aneta (Zielona Góra: Faculty of Economics and Management Press)
Face of social, economic, environmental challenges and proliferation of multi-crises - a development of social entrepreneurship, involvement and civic activism become very desirable. A need for interactions and cooperation between various groups of actors present in the local spaces is often seen as the contemporary paradigm. The aim of the study is to conceptualize the cooperation process between social enterprises and business.
Keywords: social entrepreneurship; social enterprises; business; cooperation